1982
DOI: 10.1111/j.1751-1097.1982.tb04392.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Photochemical Properties of Some Cinnamate Sunscreens by Steady State and Laser Flash Photolysis

Abstract: The E⇄ Z photoisomerization of 4′‐methoxycinnamates, used as sunscreens in cosmetics, has been studied by steady state and laser flash photolysis, in aqueous and organic solutions. Photoisomerization quantum yields are found to be fairly high (˜0.5‐1), although no intermediate is detected upon laser flash photolysis. Cinnamates are not photodynamic sensitizers but are able to quench the 8‐methoxy‐psoralen and 5‐methoxypsoralen triplets which produces E → Z isomerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 15 publications
(2 reference statements)
3
30
1
Order By: Relevance
“…5). This result is in agreement with available data in the literature [25–27]. According to [25], after irradiation, OMC shows moderate degradation (18.7%) in non‐polar solvents (mineral oil and iso propyl miristate), whereas in polar hydroalcoholic solvent (ethanol/water), 39% degradation of the molecule is observed.…”
Section: Resultssupporting
confidence: 92%
“…5). This result is in agreement with available data in the literature [25–27]. According to [25], after irradiation, OMC shows moderate degradation (18.7%) in non‐polar solvents (mineral oil and iso propyl miristate), whereas in polar hydroalcoholic solvent (ethanol/water), 39% degradation of the molecule is observed.…”
Section: Resultssupporting
confidence: 92%
“…Detailed study of the E % Z isomerization of some benzylidene camphor derivatives has been published by the authors (1,2); the same type of study with a cinnamic acid derivative has been reported (3). Similarly, several works have been devoted to the study of p-aminobenzoic acid photodecomposition (4) and one of its N,N-disubstituted esters (5,6).…”
Section: Introductionmentioning
confidence: 94%
“…However, transfer from one excited triplet state to another is possible, provided the energy levels are suitable (the triplet state energies of avobenzone and OMC are 250 kJ/mol and 239 kJ/mol, respectively [6]). Indeed, in a number of studies, OMC has been regarded as a relatively photostable compound [7][8][9]. It has been reported that triplet-triplet energy transfer is not only the mechanism for the photostabilization of avobenzone by octocrylene, but also the mechanism for the photodegradation of avobenzone by OMC.…”
Section: Introductionmentioning
confidence: 99%